Proses Pendampingan Aktivitas Magang Bersertifikat Kampus Merdeka di Sekretariat Jenderal Dewan Perwakilan Rakyat Republik Indonesia - Hardi Alunaza; Mentari Mentari (Journal of Community Development, 2024)
This mentoring is based on the constraints faced by students, namely that many graduates from higher education institutions lack the skills sought by companies, making it difficult for them to compete in the job market. This problem forms the basis of the Merdeka Belajar Kampus Merdeka policy. The Kampus Merdeka policy encompasses several important issues that need to be addressed. Firstly, the demand for changes in the education system. Secondly, the need for improvements in the quality of education. Thirdly, the need to empower the quality of students. Lastly, the enhancement of students' innovation and creativity. The mentoring activities for the Kampus Merdeka internship process are based on the needs of students regarding the importance of having supervising lecturers who can serve as consultation points to ensure the success and effectiveness of the program. These mentoring activities are carried out from August to December 2023. The purpose of implementing this mentoring process is to ensure that a total of 50 students under the guidance of lecturers can successfully complete the program at the Secretariat General of the House of Representatives of the Republic of Indonesia. The mentoring activities are carried out using three methods: mentoring, consultation and evaluation, as well as documentation and reporting. The results of this mentoring process indicate an improvement in the quality of internship students from the scores they obtained. Out of the five indicators set, initially, students received a score of 70 for three competencies: communication, results orientation, and specific competencies. Meanwhile, the other two competencies received a score of 80, namely cooperation and integrity. In the final results, all students received a score of 90 for four competency indicators, and for the competency of specific skills, students received a score of 85.